Proceedings of the Eighth International Scientific Conference "Intelligent Information Technologies for Industry" (IITI'24), Volume 2 - Kovalev, Sergey; Kotenko, Igor.; Sukhanov, Andrey; Li, Yin.; Li, Yao.; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2024)
This book contains the works connected with the key advances in Intelligent Information Technologies for Industry presented at IITI 2024, the Eighth International Scientific Conference on Intelligent Information Technologies for Industry held on November 1-7, 2024, in Harbin, China. The works were written by the experts in the field of applied artificial intelligence including topics such as Machine Learning, Explainable AI, Decision-Making, Fuzzy Logic, Multi-Agent and Bioinspired Systems including their modern applications. The following industrial implementations were touched: railway automation, cyber security, intelligent medical systems, navigation systems. The editors believe that this book will be helpful for all scientists and engineers interested in the modern state of applied artificial intelligence.
Complexity Estimate of Logical Specifications Execution for Transport Processes Prototyping -- Synthesis of an extrapolator of state parameters of dynamic processes in intelligent transport systems based on the scientific and methodological apparatus of reducing the Lagrange problem to an isoperimetric one -- Using State Transition Diagrams for Automated Knowledge Base Construction -- Planning station operations based on actual station performance obtained from the wheel.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence